Development of android-based self-assessment applications basic pencak silat techniques SMAN 1 Bengkalis - Mukhti Fadhli Kurniawan; Nurul Ihsan; Roma Irawan; Aldo Naza Putra (Jorpres (Jurnal Olahraga Prestasi), 2023)
The purpose is to determine the validity of the development of Android-based self-assessment applications in pencak silat learning and to know the reliability of the self-assessment applications developed. This type of research is development research (R D) with the development model used, namely using the ADDIE model with the research subjects of SMAN 1 Bengkalis students by taking random sampling with the number of experimental group samples of 31 students and control group samples of 30 students. The data collection instrument uses expert validation questionnaires, documentation and tests of basic pencak silat techniques. Data analysis technique using rater aiken score analysis. The results of this study were filling out questionnaires by 3 martial arts experts obtained a value of 0.778 with a valid category, 3 measurement test experts obtained a value of 0.74 with a high category, 3 material curriculum experts obtained a value of 0.814 with a high category and 3 evaluation experts obtained a value of 0.74 with a high category. In the T test, the results of Tcount 26.54 Ttable 2.00 were found where there was a difference between the experimental group and the control group. So it can be concluded that the android-based self-assessment application on the basic pencak silat technique is valid and can be used as an assessment medium used by teachers in assessing students.